Making history : a novel - Fry, Stephen, 1957- (Random House, 1998)
Michael Young is convinced his brilliant history thesis will win him a doctorate, a pleasant academic post, a venerable academic publisher and his beloved girlfriend Jane. A historian should know better than to imagine that he can predict the future.